Does Divulgation of Corporate Social Responsibility Information Influence Earnings Response Coefficient? - Hardiana, Nadhira (EQUITY, 2021)
Companies that have reported on their social responsibility activities certainly expect an increase in the Firm value. The profits generated by the company have the power of response. The market response to earnings information can be seen from the size of the Earnings Response Coefficient (ERC). This research aims to examine if the divulgation of Corporate Social Responsibility (CSR) information influenced the ERC. CSR disclosure is measured using a dichotomous method, while ERC is obtained from the regression between Cumulative Abnormal Return (CAR) and Unexpected Earning (UE). The findings of this research show that the divulgation information of CSR in the sustainability reports has no effect on the ERC.